Urgensi Regulasi Eksekusi Pidana Denda di Bidang Perpajakan Pasca Undang-Undang Cipta Kerja - Arief Sultony (Universitas Batanghari Jambi, 2021)
Job Creation Law has removed Article 13 paragraph (5) and Article 15 paragraph (4) of General Provision and Tax Procedures (KUP) Law. The absence of these articles may result in state financial loss recovery in taxation cannot be recovered. This research will identify how the regulation on the execution of tax fines related to the recovery of state financial loss before Job Creation Law was enacted and the consequences of Job Creation Law implementation on state financial losses recovery caused by tax crime. By applying the normative legal method, this research will propose the solution to the problem. The findings indicate that the KUP Law does not specifically regulate the execution of fines, so that there is a possibility that the fines will not be paid. However, based on Article 13 paragraph (5) and Article 15 paragraph (4) of the KUP Law, the state financial loss recovery can be imposed through tax assessment after court decision has permanent legal force. The elimination of these articles by Job Creation Law has the risk that the state financial losses cannot be recovered. Therefore, regulation in tax criminal fines execution is urgently required so that state financial losses can be recovered.